Efeito do sildenafil na prevenção da osteonecrose de mandíbula induzida por bifosfonatos. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
Objectives: Evaluate the prophylactic effect of the administration of sildenafil after tooth extraction, in the terapy of medication-related jaw osteonecrosis (MRONJ) in rats submitted to systemic treatment with zoledronic acid (AZ). Methodology: Thirty male Wistar rats were divided into three equal groups: C (saline, n=10), BF (AZ + saline, n=10) and SIL (AZ + SIL, n=10). The experiment was started (day 0) with the application of AZ 0.1 mg/kg twice a week for 12 weeks. In the 5th week, the SIL group started prophylaxis with 10mg/kg/day of sildenafil. One week after starting prophylaxis, all groups underwent tooth extraction. At the end of week 12, all animals were euthanized and samples were collected. The presence and severity of osteonecrosis were evaluated by clinical, imaging and histological analysis of the jaw. In addition, was analyzed the local blood flow and serum bone alkaline phosphatase levels. Results: Prophylactic treatment with sildenafil significantly reduced the incidence of ulcers, erythema, edema, necrotic area, number of empty gaps and increased the gradual repair, number of osteocytes and serum alkaline phosphatase levels when compared to the BF group (p<0, 05). Conclusions: Sildenafil has positive effects on bone remodeling, which improves healing. Therefore, it can be used as an adjuvant in the prevention of MRONJ.
Keywords: Bifosfonatos; Cirurgia Bucal; Inibidores da Fosfodiesterase; Osteonecrose; Reparo ósseo alveolar; Bisphosphonates; Oral Surgery; Phosphodiesterase Inhibitors; Osteonecrosis; Alveolar bone repair; CNPQ::CIENCIAS DA SAUDE